2014
DOI: 10.1016/j.tine.2014.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Neural basis of learning from television in young children

Abstract: It has been shown that preschool children can learn as well from video presentations as from live presentations in word acquisition, action imitation, and object searching. Several cognitive theories have been proposed to explain the developmental changes accompanying the onset of learning from TV, but the underlying neural mechanism is unclear. One possible mechanism is the mirror-matching system, in which observation of action recruits an observer's internal motor representation of the same action. Using nea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Results for the 3-years-old indicated that only some 3-years-old who passed the task showed significant activation in the right inferior PFC. In contrast, 5-years-old and adults showed this activation bilaterally (see also Moriguchi and Hiraki, 2014 ). This finding was consistent with another longitudinal study ( Moriguchi and Hiraki, 2011 ) testing children at the age of 3 and 4 years.…”
Section: Development Of Cognitive Flexibilitymentioning
confidence: 95%
“…Results for the 3-years-old indicated that only some 3-years-old who passed the task showed significant activation in the right inferior PFC. In contrast, 5-years-old and adults showed this activation bilaterally (see also Moriguchi and Hiraki, 2014 ). This finding was consistent with another longitudinal study ( Moriguchi and Hiraki, 2011 ) testing children at the age of 3 and 4 years.…”
Section: Development Of Cognitive Flexibilitymentioning
confidence: 95%
“…Specifically, Nishiyori et al found that 12-month-old infants showed more localized and a greater change in HbO concentration during reaching and more widespread but a greater HbO responses during stepping than 6-month-old infants ( 96 ). From school age to adulthood, children demonstrated increased left-lateralization during motor tasks and different hemodynamic patterns when learning from live versus televised models ( 97 , 98 ). Specifically, Su et al measured hemodynamic responses in the frontal, temporal, and parietal cortex, and found greater right hemispheric activation during action observation, but less left hemispheric activation during action and imitation in children compared to adults ( 97 ).…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, Su et al measured hemodynamic responses in the frontal, temporal, and parietal cortex, and found greater right hemispheric activation during action observation, but less left hemispheric activation during action and imitation in children compared to adults ( 97 ). On the other hand, Moriguchi et al found greater left primary cortex activation in children when learning from live vs. televised models, whereas adults showed similar bilateral primary cortex activation regardless of the types of the learning model ( 98 ).…”
Section: Resultsmentioning
confidence: 99%
“…It is little known whether traditional animation plays a different role from computer animation in children's viewing experience and learning, less so in their EF. In other fields, researchers have noted that young children prefer to imitate and learn from a live model or a teacher rather than a mechanical model or a robot (e.g., Meltzoff, 1995;Kuhl et al, 2003;Moriguchi and Hiraki, 2014). A similar line of research is worth pursuing to detect children's preferences for traditional or computer animation technology.…”
Section: Discussionmentioning
confidence: 99%